The role of the immune response in developing tuberculosis infection: from latent infection to active tuberculosis - Kudryavtsev, Igor; Starshinova, Anna; Rubinstein, Artem; Kulpina, Anastasia; Ling, Hong; Zhuang, Min; Kudlay, Dmitry (Frontiers in Tuberculosis, 2024)
Despite advancements in modern medicine, tuberculosis continues to be one of the leading causes of death globally. Findings indicate that COVID-19 may trigger the activation of tuberculosis infection (TB), leading to its spread. Despite the development of new immunological diagnostic methods for latent tuberculosis infection (LTBI), it is still unclear how the infection transitions to an active TB state. The goal of the study is to provide insights into the progression of tuberculosis infection from a latent to an active state. This article presents recent research data focused on investigating the pathogenesis of LTBI, particularly the immune responses in the interaction between Mycobacteria tuberculosis (Mtb) and the host. It describes the mechanisms of T-cell immunity and cytokine activation, supporting the concept of type 1, type 2, and type 3 immune responses. According to the conducted studies, Th17 cells have a significant role in the development of type 3 antigen-specific responses. The cytokines IL-6 and IL-23 activate STAT3, which is necessary to trigger the expression of Th17. Future research on the role of Th17 cells and cytokines, particularly IL-6 and IL-21, may be beneficial in understanding the shift from LTBI to active TB.